2021
DOI: 10.1002/phar.2518
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin versus unfractionated heparin for venous thromboembolism prophylaxis in renally impaired ICU patients

Abstract: Introduction Intensive care unit (ICU) patients with renal insufficiency are more likely to develop venous thromboembolism and are at an increased risk for bleeding. There is conflicting data on whether enoxaparin or unfractionated heparin (UFH) is preferred for preventing thromboembolism in this population. Therefore, the purpose of this study was to evaluate the safety of prophylactic enoxaparin versus UFH in ICU patients with renal impairment. Methods We conducted a single‐center, retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A single‐center retrospective study evaluating enoxaparin versus UFH for VTE prophylaxis in critically ill patients with impaired renal function noted that the use of enoxaparin was associated with an increased risk of major bleeding compared with UFH. It should be noted, however, that this study included patients with AKI, severely decreased renal function, and ESRD 9 . A recent study evaluating bleeding events in hospitalized patients receiving apixaban found no difference in the rate of major bleeding events between patients with and without AKI, although the study may have been underpowered.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A single‐center retrospective study evaluating enoxaparin versus UFH for VTE prophylaxis in critically ill patients with impaired renal function noted that the use of enoxaparin was associated with an increased risk of major bleeding compared with UFH. It should be noted, however, that this study included patients with AKI, severely decreased renal function, and ESRD 9 . A recent study evaluating bleeding events in hospitalized patients receiving apixaban found no difference in the rate of major bleeding events between patients with and without AKI, although the study may have been underpowered.…”
Section: Introductionmentioning
confidence: 92%
“…Baseline patient characteristics are represented in Table 1. The median hospital length of stay was 6 [3-9.5] versus 8 [5][6][7][8][9][10][11][12][13][14] days in the factor Xa inhibitor group compared with the UFH group, respectively (p < 0.001). Chronic kidney disease was common, present in 50.8% of factor Xa inhibitor patients and 43.6% of UFH patients.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective, single-center, cohort study including 460 ICU patients with renal impairment, DVT prophylaxis was administered with either enoxaparin or UFH, it was found that use of enoxaparin for thromboprophylaxis in renally impaired critically ill patients, was associated with an increase in major bleeding events compared to UFH. 76 …”
Section: S Ummary Of R Ecommendationsmentioning
confidence: 99%
“…Current pharmacological thromboprophylaxis in the ICU setting is based on either unfractionated heparin (UFH) or low-molecular-weight heparins (LMWHs). Extensive studies have shown that LMWHs are as effective as UFH in reducing the incidence of thrombotic complications in critically ill patients, but carry less risk of bleeding, and heparin-induced thrombocytopenia (HIT) than UFH [ 5 ]; therefore, LMWHs are more readily used anticoagulant agents in the ICU population. Enoxaparin, dalteparin, and tinzaparin are widely used LMWH agents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%